2005
DOI: 10.1186/1465-9921-6-66
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol extract attenuates lung injury in experimental model of carrageenan-induced pleurisy in mice

Abstract: Here we investigate the effects of the green tea extract in an animal model of acute inflammation, carrageenan-induced pleurisy. We report here that green tea extract (given at 25 mg/kg i.p. bolus 1 h prior to carrageenan), exerts potent anti-inflammatory effects in an animal model of acute inflammation in vivo.Injection of carrageenan (2%) into the pleural cavity of mice elicited an acute inflammatory response characterized by fluid accumulation in the pleural cavity that contained many neutrophils (PMNs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 51 publications
(51 reference statements)
2
45
0
Order By: Relevance
“…Our observation suggests that green tea extract, when administered with reserpine, may result in kidney remedial, which, therefore, appears to be responsible for reports exist in literature, supporting the role of green tea in oxidative stress-damage recovery in animal models (Das et al, 2002;Baltaziak et al, 2004;Chen et al, 2004;Di Paola et al, 2005;Hisamura, et al, 2006;Itoh et al, 2005;Yokozawa et al, 2005;Upaganlawar et al, 2006). Green tea extract represents a rich source of natural polyphenols that has in vivo protective effects on liver and serum.…”
Section: Figmentioning
confidence: 79%
“…Our observation suggests that green tea extract, when administered with reserpine, may result in kidney remedial, which, therefore, appears to be responsible for reports exist in literature, supporting the role of green tea in oxidative stress-damage recovery in animal models (Das et al, 2002;Baltaziak et al, 2004;Chen et al, 2004;Di Paola et al, 2005;Hisamura, et al, 2006;Itoh et al, 2005;Yokozawa et al, 2005;Upaganlawar et al, 2006). Green tea extract represents a rich source of natural polyphenols that has in vivo protective effects on liver and serum.…”
Section: Figmentioning
confidence: 79%
“…P-selectin (CD62P; BD Pharmingen), myeloperoxidase, ICAM-1 (CD54; BD Pharmingen), and nitrotyrosine Abs (Upstate Biotechnology) were used, as previously described (33). The polyclonal anti-GITR (R&D Systems) and anti-ZO-1 Abs were used 1/100 in the same experimental conditions as the others.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Tissue sections were prepared, as previously described (33). P-selectin (CD62P; BD Pharmingen), myeloperoxidase, ICAM-1 (CD54; BD Pharmingen), and nitrotyrosine Abs (Upstate Biotechnology) were used, as previously described (33).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent amount is active and shows an interesting bioavailability ranging from 4.5% for gallic acid to 8.7% for (À)-epigallocatechingallate (EGCG) and EGC. The biological activities of tea polyphenols include antioxidative capability on LDL, antiatherosclerotic, hypocholesterolaemic, antihypertensive, antiallergic, antimicrobial, and anticarcinogenic properties [7][8][9][10][11]. Several studies [12,13] demonstrated that tea catechins can scavenge reactive oxygen species (ROS), thanks to the phenolic hydroxyl group present in the flavan-3-ol structure, and also prevent their formation by inhibiting the xanthine oxidase [14].…”
Section: Introductionmentioning
confidence: 99%